PENGARUH MUTASI, BUDAYA ORGANISASI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP MOTIVASI KERJA DAN KINERJA PEGAWAI PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG DI WILAYAH PROVINSI JAWA TIMUR - L, Muhamad Syaiful; Tobing, Diana Sulianti; Prihatini, Dewi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract: The objective of this study is to determine the effect of mutation, organizational culture, and transformational leadership on work motivation and employees performance in The Office of State Assets and Auction Service in East Java Province. The samples were consisted of 176 employees. Structural Equation Modeling (SEM) was employed as the method of analysis. The results showed that mutation has significant effect on work motivation, organizational culture has significant effect on work motivation, but transformational leadership does not have significant effect on work motivation. Mutation has significant effect on employee performance, organizational culture has significant effect on employee performance, but transformational leadership does not have significant effect on employee performance. Keywords:Mutation, Organizational Culture, Transformational Leadership, Work Motivation, and Employees Performance